Instrument for the evaluation of education at work in the Comprehensive Attention to the Population subject - Ana Gloria Vázquez De León; Alfredo Alberto Espinosa Roca; Lisgrace Llano Arana; Yoel González Beriau; Annia Lourdes González Armenteros; Dailys García Morales (Medisur)
Background: in the current context of higher medical education, it is necessary to develop a participatory evaluation methodology in the various practical-clinical teaching scenarios of the training process that allows overcoming the traditional forms that have historically been based on the identification of knowledge and skills. Objective: to propose an instrument to evaluate the students` learning in the education at work of the Comprehensive Attention to the Population subject, that is taught in the fifth year of the Stomatology career. Methods: pedagogical research developed at the Cienfuegos University of Medical Sciences. Theoretical methods were used: analytical-synthetic and inductive-deductive and empirical: documentary analysis, interviews with teachers of the subject and participatory techniques. The proposed instrument was evaluated according to the criteria of specialists. Results: a rubric was made in correspondence with the system of main skills to be mastered declared in the program of the subject. For each nucleus, a score was established according to the level of execution or its domain. It allows hetero-evaluation, co-evaluation and self-evaluation, by providing the student with the possibility of recognizing their progress, achievements and difficulties, analyzing their individual and group situation in said educational process and developing a critical and reflective attitude about their educational process. Conclusions: the rubric is, undoubtedly, one of the instruments with the greatest potential for learning, it enables the evaluation of the objectives` degree of fulfillment.